(untitled) (Biological Sciences - PJSIR, 1994)
Atomic absorption spectroscopy (AAS) was found to be a suitable method for the estimation of iron, copper, zinc, magnesium, aluminium and lead in urinary calculi; graphite furnace electrothermal atomisation was required for lead and flame atomisation for the others. A standard urinary stone solution was made up and calibrated for each element using the method of standard additions. In all case, absorption varied linearly with concentration; reproducibility, accuracy and recovery were satisfactory for all elements. Conventional atomic absorption standards in 1%nitric acid solution had low apparent analyte concentrtions against the standard stone solution. If those were used as primary standards it was found that apprent values as a percentage of the true values would be: Fe, 108.5; Cu, 103.1; Zn, 106.4; Mg, 125.0; AI, 103.6; Pb, 102.2%. Also, apparent concentrations of magnesium, zinc and copper in dilute nitric acid solution varied significantly with acid strength. It was concluded that in order to minimise matrix and pH effects, urinary stone analysis should only be done against standard urinary stone solution.